Composite catalytic material as well as preparation method and application thereof
By combining electron-deleted elecological compounds with electron-derived transition metal phthalocyanine complexes to form a composite catalytic material, the problem of insufficient activity of transition metal phthalocyanine complexes in polymerization reaction is solved, and catalytic activity and efficiency are significantly improved.
Patent Information
- Application Number
- CN202411324262.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
AI Technical Summary
The transition metal phthalocyanine complex itself has no activity to catalyze polymerization, limiting its application in polymerization.
By combining electron-deleting electrons with electron-derived transition metal phthalocyanine complexes through electrostatic attraction, a composite catalytic material is formed, and the valence of transition metal elements is reduced, thereby promoting the formation of active radical intermediates in the polymerization reaction.
The catalytic activity and efficiency of the polymerization reaction are improved, especially in polymerization reactions such as methyl methacrylate and styrene, which significantly improves the catalytic efficiency.
Smart Images

Figure CN119241749A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysis, and in particular to a composite catalytic material and a preparation method and application thereof. Background Art
[0002] Polymerization reactions are crucial in the production of bulk chemicals. For example, methyl methacrylate is used to polymerize to produce polymethyl methacrylate (PMMA for short). PMMA has good light transmittance, electrical insulation, solvent resistance, and weather resistance. After post-processing, it can be used in liquid crystal light guide plates, LED lamps, optical fiber materials, optical products, auto parts, home appliance parts, and daily necessities. Another example is the polymerization of styrene to produce polystyrene, which also has a wide range of applications in various fields.
[0003] Catalysts are often required in polymerization reactions. Transition metal phthalocyanine complexes (MPc), in which the transition metal is coordinated with the four nitrogen atoms in the center of the phthalocyanine molecule to form a planar tetragonal configuration, exhibit excellent thermal stability and solvent stability, and have outstanding applications in magnetism, optics, electrochemistry, and catalytic reactions. Such complexes usually have a rich redox state, as well as a controllable metal center and ligand environment. However, studies have shown that transition metal phthalocyanine complexes themselves do not have the activity of catalyzing polymerization reactions (such as methyl methacrylate polymerization reactions). Therefore, it would be of great significance if transition metal phthalocyanine complexes could be modified and utilized for catalytic polymerization reactions. Summary of the invention
[0004] Based on the above-mentioned deficiencies of the prior art, the purpose of the present invention is to provide a composite catalytic material and a preparation method and application thereof, aiming to solve the problem that the transition metal phthalocyanine complex itself has no activity in catalyzing polymerization reactions.
[0005] The technical solution of the present invention is as follows:
[0006] In a first aspect of the present invention, a composite catalytic material is provided, wherein the composite catalytic material comprises an electron-losing electron compound and an electron-gaining transition metal phthalocyanine complex that is combined with the electron-losing electron compound by electrostatic attraction;
[0007] The valence of the transition metal element in the transition metal phthalocyanine complex that gains electrons is lower than the valence of the transition metal element in the transition metal phthalocyanine complex when the transition metal phthalocyanine complex does not gain electrons.
[0008] Optionally, the electronic compound includes calcium heptadoaluminate electronic compound, Y 5 Si 3 , LaCu 0.67 Si 1.33 、LaNi 0.5Si 1.5 、LaCoSi、LaRuSi、LaH 2 , Ca 2 N and Y 2 At least one of C.
[0009] Optionally, the transition metal phthalocyanine complex includes at least one of cobalt phthalocyanine, iron phthalocyanine, sulfonated cobalt phthalocyanine and amino cobalt phthalocyanine.
[0010] Optionally, the valence of the transition metal element in the electron-accepting transition metal phthalocyanine complex is +1.
[0011] The second aspect of the present invention provides a method for preparing the composite catalytic material as described above, which comprises the following steps:
[0012] adding a transition metal phthalocyanine complex and an electronic compound into an organic solvent to obtain a mixed solution;
[0013] The mixed solution is ball-milled to obtain the composite catalytic material.
[0014] Optionally, the electronic compound includes calcium heptadoaluminate electronic compound, Y 5 Si 3 , LaCu 0.67 Si 1.33 、LaNi 0.5 Si 1.5 、LaCoSi、LaRuSi、LaH 2 , Ca 2 N and Y 2 C; the transition metal phthalocyanine complex includes at least one of cobalt phthalocyanine, iron phthalocyanine, sulfonated cobalt phthalocyanine and amino cobalt phthalocyanine; the organic solvent includes at least one of N,N-dimethylformamide and methanol.
[0015] Optionally, the rotation speed of the ball mill is 300-600 rpm; during the ball milling process, the material is allowed to stand for 30 minutes after each 30 minutes of ball milling, and the total time of ball milling and standing is 6-12 hours.
[0016] Optionally, the mass ratio of the transition metal phthalocyanine complex to the electronic compound is 1:(5-20).
[0017] The fourth aspect of the present invention provides a use of the composite catalytic material as described above in the present invention and / or the composite catalytic material prepared by the preparation method as described above in the present invention in a catalytic polymerization reaction.
[0018] Optionally, the polymerization reaction is a methyl methacrylate polymerization reaction or a styrene polymerization reaction.
[0019] Beneficial effect: In the present invention, the electron-losing electronic compound and the electron-gaining transition metal phthalocyanine complex are combined through electrostatic attraction to form a composite catalytic material. The transition metal in the composite catalytic material is a low-valent transition metal, which can promote the generation of active free radical intermediates during the polymerization reaction, has good catalytic activity, and has a high catalytic efficiency for the polymerization reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The X-ray diffraction patterns of the composite catalytic materials prepared in Examples 1 to 4, wherein (a) is the CoPc@C12A7:e in Example 1. - and FePc@C12A7:e in Example 2 - X-ray diffraction pattern of CoPc@Y in Example 3 5 Si 3 and FePc@Y in Example 4 5 Si 3 X-ray diffraction pattern of .
[0021] Figure 2 The scanning electron microscope and energy dispersive spectrometer analysis images of the composite catalytic materials prepared in Examples 1 to 4, wherein (a) is the CoPc@C12A7:e in Example 1 - SEM and EDS analysis diagram; (b) FePc@C12A7:e in Example 2 - SEM and EDS analysis diagram, (c) CoPc@Y in Example 3 5 Si 3 SEM and EDS analysis diagram, (d) FePc@Y in Example 4 5 Si 3 Scanning electron microscope and energy dispersive spectrometer analysis diagram.
[0022] Figure 3 (a) is the UV-visible absorption spectrum of the solution after ball milling in the process of preparing the composite catalytic material in Example 1, and (b) is the UV-visible absorption spectrum of the solution after ball milling in the process of preparing the composite catalytic material in Example 2.
[0023] Figure 4 The X-ray photoelectron spectra of the composite catalytic materials prepared in Examples 1 to 4 are shown in Figure 1, wherein (a) is the CoPc@C12A7:e in Example 1. - and CoPc@Y in Example 3 5 Si 3 X-ray photoelectron spectrum of FePc@C12A7:e in Example 2. - and FePc@Y in Example 45 Si 3 X-ray photoelectron spectrum of .
[0024] Figure 5 is the CoPc@C12A7:e in Example 1 - and CoPc@Y in Example 3 5 Si 3 Magnetic susceptibility test chart. DETAILED DESCRIPTION
[0025] The present invention provides a composite catalytic material and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0026] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0027] An embodiment of the present invention provides a composite catalytic material, wherein the composite catalytic material includes an electron-losing electron compound and an electron-gaining transition metal phthalocyanine complex that is combined with the electron-losing electron compound through electrostatic attraction;
[0028] The valence of the transition metal element in the transition metal phthalocyanine complex that gains electrons is lower than the valence of the transition metal element in the transition metal phthalocyanine complex when the transition metal phthalocyanine complex does not gain electrons (i.e., if the valence state of the transition metal element in the transition metal phthalocyanine complex is +2 when no electrons are gained, the valence of the transition metal element in the transition metal phthalocyanine complex that gains electrons is lower than +2, for example, can be +1).
[0029] In the present invention, the electron-losing electron compound and the electron-gaining transition metal phthalocyanine complex are combined through electrostatic attraction to form a composite catalytic material. The transition metal in the composite catalytic material is a low-valent transition metal, which can promote the generation of active free radical intermediates during the polymerization reaction, has good catalytic activity, and has a high catalytic efficiency for polymerization reactions (such as methyl methacrylate polymerization reactions, etc.).
[0030] In some embodiments, the electron compound comprises calcium heptadoaluminate electron compound (C12A7:e - ), Y 5 Si 3 , LaCu 0.67 Si 1.33 、LaNi 0.5 Si 1.5、LaCoSi、LaRuSi、LaH 2 , Ca 2 N and Y 2 At least one of C, but not limited thereto.
[0031] In some embodiments, the transition metal phthalocyanine complex includes at least one of cobalt phthalocyanine, iron phthalocyanine, sulfonated cobalt phthalocyanine, and aminocobalt phthalocyanine, but is not limited thereto.
[0032] In some embodiments, the valence of the transition metal element in the electron-accepting transition metal phthalocyanine complex is +1.
[0033] The present invention also provides a method for preparing the composite catalytic material of the present invention, which comprises the following steps:
[0034] S1, adding a transition metal phthalocyanine complex and an electronic compound into an organic solvent to obtain a mixed solution;
[0035] S2. Ball milling the mixed solution to obtain the composite catalytic material.
[0036] In the embodiment of the present invention, a ball milling method is adopted to prepare a composite catalytic material using a transition metal phthalocyanine complex (electron gainer) and an electronized substance (electron donor) as raw materials. Specifically, during the ball milling of the mixed solution, the electrons of the electronized substance can be effectively transferred to the transition metal phthalocyanine complex, so that the valence state of the transition metal changes from a high valence state to a low valence state (such as from +2 valence to +1 valence), and the color of the solution changes. Since some electrons are missing from the surface of the electronized substance, the transition metal phthalocyanine complex that obtains electrons presents a negative charge as a whole, and the two are combined by strong electrostatic attraction to form a stable composite catalytic material. The preparation method is simple, easy to operate, low in cost, and has universality and promotion. At the same time, the transition metal in the prepared composite catalytic material is a low-valent transition metal, which can promote the generation of active free radical intermediates during the polymerization reaction, has good catalytic activity, and has a high catalytic efficiency for polymerization reactions (such as methyl methacrylate polymerization, styrene polymerization, etc.).
[0037] In step S1, in some embodiments, the electronic compound includes C12A7:e - , Y 5 Si 3 , LaCu 0.67 Si 1.33 、LaNi 0.5 Si 1.5 、LaCoSi、LaRuSi、LaH 2 , Ca 2 N and Y 2C, but not limited thereto; the transition metal phthalocyanine complex includes at least one of cobalt phthalocyanine, iron phthalocyanine, sulfonated cobalt phthalocyanine and amino cobalt phthalocyanine, but not limited thereto; the organic solvent includes at least one of N,N-dimethylformamide and methanol, but not limited thereto.
[0038] In some embodiments, the mass ratio of the transition metal phthalocyanine complex to the electronic compound is 1:(5-20). For example, the mass ratio of the transition metal phthalocyanine complex to the electronic compound may be 1:5, 1:10, 1:15 or 1:20.
[0039] In step S1, in some specific embodiments, under an inert gas protective atmosphere, a transition metal phthalocyanine complex and an electronic compound are added to an organic solvent to obtain a mixed solution.
[0040] In some embodiments, the concentration of the transition metal phthalocyanine complex in the mixed solution is 0.5 to 2.5 mg / mL. For example, the concentration of the transition metal phthalocyanine complex in the mixed solution may be 0.5 mg / mL, 1 mg / mL, 1.5 mg / mL, 2.0 mg / mL or 2.5 mg / mL.
[0041] In step S2, in some embodiments, the rotation speed of the ball mill is 300-600 rpm (for example, 300 rpm, 400 rpm, 500 rpm or 600 rpm, etc.); during the ball milling process, the ball mill is left to stand for 30 minutes after each 30 minutes of ball milling, and the total time of ball milling and standing is 6-12 hours (for example, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, etc.). That is, the following steps are performed during the ball milling process:
[0042] S21, ball milling for 30 min, let stand for 30 min;
[0043] S22, repeat step S1 several times until the total time of ball milling and standing is 6 to 12 hours.
[0044] Such ball milling can make the transition metal phthalocyanine complex and the electronic compound more closely compounded, wherein, standing still can prevent the overheating of the ball milling for a long time from affecting the product and the equipment.
[0045] In some embodiments, after ball-milling the mixed solution, before obtaining the composite catalytic material, the process further includes filtering the ball-milled product and vacuum drying the filtered solid.
[0046] The embodiment of the present invention also provides an application of the composite catalytic material as described above in the embodiment of the present invention and / or the composite catalytic material prepared by the preparation method as described above in the embodiment of the present invention in catalytic polymerization. In the embodiment of the present invention, the transition metal in the composite catalytic material is a low-valent transition metal, which can promote the generation of active free radical intermediates during the polymerization reaction and has good catalytic activity.
[0047] In some embodiments, the polymerization reaction is a methyl methacrylate polymerization reaction or a styrene polymerization reaction.
[0048] The present invention will be further described below by means of specific examples.
[0049] Example 1
[0050] This embodiment provides a composite catalytic material (denoted as CoPc@C12A7:e - ) comprising the steps of:
[0051] In a glove box under argon protection, 5 mg of cobalt phthalocyanine (CoPc) was dispersed in 2 mL of N,N-dimethylformamide, followed by the addition of 50 mg of C12A7:e - Electron the substance to obtain a mixture;
[0052] The mixture was transferred to a ball milling jar lined with zirconium oxide and sealed, and ball milled at a rotation speed of 400 rpm, wherein the ball milling was paused for 30 minutes after every 30 minutes, and the total ball milling and pause time was 8 hours;
[0053] The ball mill was opened in the glove box, the product obtained by ball milling was filtered, and the filtered solid was vacuum dried in the glove box to finally obtain CoPc@C12A7:e - .
[0054] Example 2
[0055] This embodiment provides a composite catalytic material (denoted as FePc@C12A7:e - ) comprising the steps of:
[0056] In a glove box under argon protection, 5 mg of iron phthalocyanine (FePc) was dispersed in 2 mL of N,N-dimethylformamide solution, and then 50 mg of C12A7:e was added. - Electron the substance to obtain a mixture;
[0057] The mixture was transferred to a ball milling jar lined with zirconium oxide and sealed, and ball milled at a rotation speed of 400 rpm, wherein the ball milling was paused for 30 minutes after every 30 minutes, and the total ball milling and pause time was 8 hours;
[0058] The ball mill was opened in the glove box, the product obtained by ball milling was filtered, and the filtered solid was vacuum dried in the glove box to finally obtain FePc@C12A7:e - .
[0059] Example 3
[0060] This embodiment provides a composite catalytic material (denoted as CoPc@Y 5 Si 3 ) comprising the steps of:
[0061] In a glove box under argon protection, 5 mg of cobalt phthalocyanine (CoPc) was dispersed in 2 mL of N,N-dimethylformamide solution, and then 50 mg of Y 5 Si 3 Electron the substance to obtain a mixture;
[0062] The mixture was transferred to a ball milling jar lined with zirconium oxide and sealed, and ball milled at a rotation speed of 400 rpm, wherein the ball milling was paused for 30 minutes after every 30 minutes, and the total ball milling and pause time was 8 hours;
[0063] The ball mill was opened in the glove box, the product obtained by ball milling was filtered, and the filtered solid was vacuum dried in the glove box to finally obtain CoPc@Y 5 Si 3 .
[0064] Example 4
[0065] This embodiment provides a composite catalytic material (denoted as FePc@Y 5 Si 3 ) comprising the steps of:
[0066] In a glove box under argon protection, 5 mg of iron phthalocyanine (FePc) was dispersed in 2 mL of N,N-dimethylformamide solution, and then 50 mg of Y 5 Si 3 Electron the substance to obtain a mixture;
[0067] The mixture was transferred to a ball milling jar lined with zirconium oxide and sealed, and ball milled at a rotation speed of 400 rpm, wherein the ball milling was paused for 30 minutes after every 30 minutes, and the total ball milling and pause time was 8 hours;
[0068] The ball mill was opened in the glove box, the mixture was filtered, the obtained product was filtered, and the obtained solid was vacuum dried in the glove box to finally obtain FePc@Y 5 Si 3 .
[0069] test:
[0070] (1) The X-ray diffraction patterns of the composite catalytic materials prepared in Examples 1 to 4 are as follows: Figure 1 As shown. It can be seen that the composite catalytic material CoPc@C12A7:e was successfully prepared by Examples 1 to 4. - 、FePc@C12A7:e - 、CoPc@Y 5 Si 3 、FePc@Y 5 Si 3 Specifically, the main phases of the composite catalytic materials prepared in Examples 1 to 4 are C12A7:e - 、C12A7:e - , Y 5 Si 3 , and Y 5 Si 3 The low-angle diffraction peaks indicate that the composite catalytic material CoPc@C12A7:e - 、CoPc@Y 5 Si 3 There is a small amount of CoPc crystals in the molten metal.
[0071] (2) The scanning electron microscope images and energy dispersive spectrometer scanning results of the composite catalytic materials prepared in Examples 1 to 4 are as follows: Figure 2 It can be seen that the transition metal elements in the composite catalytic material prepared in the above examples are uniformly distributed on the surface of the electronic compound, confirming the composite of the transition metal complex and the electronic compound.
[0072] (3) In the process of preparing the composite catalytic material in Example 1 and Example 2, the UV-visible absorption spectrum test results of the solution after ball milling are as follows Figure 3 Compared with the solution of pure cobalt phthalocyanine (CoPc), the absorption spectrum of cobalt phthalocyanine in Example 1 after adding the electron compound (i.e., the solution after ball milling) showed a new absorption peak (466nm) and a red shift of the absorption peak (658nm to 699nm), which corresponded to the charge transfer from +1-valent Co ions to phthalocyanine ligands and the Q band absorption (π-π *Transition). Compared with the solution of pure iron phthalocyanine (FePc), the absorption spectrum of iron phthalocyanine in Example 2 after adding the electronized substance (i.e., the solution after ball milling) showed new absorption peaks centered at 518nm and 809nm, which correspond to the charge transfer from +1 valent iron ions to Pc ligands in the solution and other charge transfers. The above results show that there is an electron transfer phenomenon from the electronized substance to cobalt phthalocyanine or iron phthalocyanine during the preparation process of the composite catalytic material, and the electrons are transferred from the electronized substance to the transition metal ion center of cobalt phthalocyanine or iron phthalocyanine. This result shows that the valence state of the transition metal in the composite catalytic material prepared in Examples 1 to 4 is in a low valence state of +1.
[0073] (4) The X-ray photoelectron spectroscopy test results of the composite catalytic materials prepared in Examples 1 to 4 are shown in FIG. Figure 4 Compared with the spectra of cobalt phthalocyanine (CoPc) or iron phthalocyanine (FePc), the binding energy of all composite catalytic materials shifts to low energy, indicating that the valence state of the transition metal in the composite catalytic material prepared in the above embodiment is in a low valence state of +1.
[0074] (5) The magnetic susceptibility test results of the composite catalytic materials prepared in Example 1 and Example 3 are as follows Figure 5 Compared with the magnetic susceptibility of cobalt phthalocyanine (CoPc), the magnetic susceptibility of the composite catalytic material shows obvious anti-magnetism, which is due to the presence of phthalocyanine D 4h The spin ground state of the symmetrical +2-valent Co ion is S=1 / 2, while all electrons in the +1-valent Co are paired, with a ground state spin S=0, exhibiting anti-magnetism. Therefore, this result indicates that the valence state of the transition metal in the composite catalytic materials prepared in Example 1 and Example 3 is in a low valence state of +1.
[0075] (6) Application in polymerization reaction
[0076] CoPc, FePc, Y 5 Si 3 、C12A7:e - And the CoPc@C12A7:e prepared in Examples 1 to 4 - 、FePc@C12A7:e - 、CoPc@Y 5 Si 3 、FePc@Y 5 Si 3 They were used as catalysts in the polymerization of methyl methacrylate (MMA).
[0077] The reaction conditions were as follows: glove box with argon protection, catalyst dosage 10 mg, initiator CCl 4The dosage is 2.4 mL, the dosage of the reaction monomer methyl methacrylate is 0.87 mL, the dosage of the reaction solvent N,N-dimethylformamide is 2 mL, the reaction temperature is 75°C, and the reaction time is 20 hours. The final product is collected by centrifuging the mixture, pouring the upper clear solution into 200 mL of methanol, and the white precipitate formed under vigorous stirring is the polymethyl methacrylate (PMMA) product, which is filtered and vacuum dried. The results are shown in Table 1.
[0078] Table 1. Catalytic performance of each catalyst
[0079]
[0080] It can be seen that CoPc, FePc, Y 5 Si 3 、C12A7:e - The composite catalytic material has no catalytic activity for the polymerization reaction of methyl methacrylate, while the composite catalytic material prepared by the preparation method provided by the present invention has good catalytic activity and good catalytic efficiency for the polymerization reaction of methyl methacrylate.
[0081] In summary, the present invention provides a composite catalytic material and its preparation method and application. In the present invention, the electron-losing electron-generated substance and the electron-gaining transition metal phthalocyanine complex are combined by electrostatic attraction to form a composite catalytic material. The transition metal in the composite catalytic material is a low-valent transition metal, which can promote the generation of active free radical intermediates during the polymerization reaction, has good catalytic activity, and has a high catalytic efficiency for the polymerization reaction. In addition, the present invention adopts a ball milling method, using a transition metal phthalocyanine complex (electron-gaining substance) and an electron-generated substance (electron-donating substance) as raw materials to prepare a composite catalytic material. During the ball milling process, the electrons of the electron-generated substance can be effectively transferred to the transition metal phthalocyanine complex, so that the valence state of the transition metal changes from a high valence state to a low valence state. Since the electron-generated substance lacks some electrons on its surface, the transition metal phthalocyanine complex that gains electrons presents a negative charge as a whole, and the two are combined by strong electrostatic attraction to form a stable composite catalytic material. The preparation method is simple and easy to implement, has low cost, and has universality and promotion.
[0082] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A composite catalytic material, characterized in that: The composite catalytic material includes an electron-losing electron compound and an electron-gaining transition metal phthalocyanine complex that is combined with the electron-losing electron compound through electrostatic attraction; The valence of the transition metal element in the transition metal phthalocyanine complex that gains electrons is lower than the valence of the transition metal element in the transition metal phthalocyanine complex when the transition metal phthalocyanine complex does not gain electrons.
2. The composite catalytic material according to claim 1, characterized in that: The electronic compound includes calcium heptadoaluminate electronic compound, Y5Si3, LaCu 0.67 Si 1.33 、LaNi 0.5 Si 1.5 , LaCoSi, LaRuSi, LaH2, Ca2N and Y2C.
3. The composite catalytic material according to claim 1, characterized in that: The transition metal phthalocyanine complex comprises at least one of cobalt phthalocyanine, iron phthalocyanine, sulfonated cobalt phthalocyanine and amino cobalt phthalocyanine.
4. The composite catalytic material according to claim 3, characterized in that: The valence of the transition metal element in the electron-accepting transition metal phthalocyanine complex is +1.
5. A method for preparing a composite catalytic material as claimed in claim 1, characterized in that: The steps include: adding a transition metal phthalocyanine complex and an electronic compound into an organic solvent to obtain a mixed solution; The mixed solution is ball-milled to obtain the composite catalytic material.
6. The preparation method according to claim 5, characterized in that: The electronic compound includes calcium heptadoaluminate electronic compound, Y5Si3, LaCu 0.67 Si 1.33 、LaNi 0.5 Si 1.5 , LaCoSi, LaRuSi, LaH2, Ca2N and Y2C; the transition metal phthalocyanine complex includes at least one of cobalt phthalocyanine, iron phthalocyanine, sulfonated cobalt phthalocyanine and amino cobalt phthalocyanine; the organic solvent includes at least one of N,N-dimethylformamide and methanol.
7. The preparation method according to claim 5, characterized in that: The rotation speed of the ball mill is 300-600 rpm; during the ball milling process, the material is allowed to stand for 30 minutes after each 30 minutes of ball milling, and the total time of ball milling and standing is 6-12 hours.
8. The preparation method according to claim 5, characterized in that: The mass ratio of the transition metal phthalocyanine complex to the electronic compound is 1:(5-20).
9. Use of the composite catalytic material according to any one of claims 1 to 4 and / or the composite catalytic material prepared by the preparation method according to any one of claims 5 to 8 in catalytic polymerization reactions.
10. The use according to claim 9, characterized in that: The polymerization reaction is a methyl methacrylate polymerization reaction or a styrene polymerization reaction.
